Sagger for sintering positive electrode material of sodium-ion battery and preparation method of sagger
By using a combined structure of the matrix layer and surface coating slurry in the sintering casing for sodium ion battery positive electrode material, the wear and pollution problems caused by deformation and reuse of traditional silos at high temperatures are solved, and better mechanical properties and corrosion resistance are achieved, extending service life and improving sintering effect.
Patent Information
- Application Number
- CN202411892520.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The sintering casing for the sintering of traditional sodium ion batteries may undergo slight deformation at high temperatures, resulting in cracks or deformation of the sintered material, and reusing it may lead to surface wear and contamination, affecting the sintering effect.
A silo consisting of a matrix layer and a surface coating slurry, which is made of mullite, alumina, cordierite and a modified refractory material. The surface coating slurry is made of strontium carbonate, modified alumina, silicon carbide and silicon nitride, and is prepared by drying and high temperature sintering.
It improves the mechanical properties and corrosion resistance of the sachet, reduces the possibility of deformation and cracks at high temperatures, extends the service life, and improves the sintering effect.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sagger kiln preparation, in particular to a sagger for sintering positive electrode materials of sodium ion batteries and a preparation method thereof. Background Art
[0002] The sagger for sintering positive electrode materials of sodium ion batteries is a container or mold specially used in the sintering process of positive electrode materials of sodium ion batteries. Its main function is to load positive electrode material powder, provide necessary protection and support in the sintering furnace, and ensure that the positive electrode material can be sintered evenly and efficiently.
[0003] Saggers are usually made of high temperature resistant and corrosion resistant materials. These materials need to be able to withstand pressure and chemical corrosion at high temperatures, and have good thermal conductivity and electrical insulation. Specifically, common materials for saggers include ceramic materials such as alumina (Al2O3) and silicon carbide (SiC). These materials have the characteristics of high purity, high strength, high hardness and high thermal stability, and are ideal for preparing saggers.
[0004] The production process of saggers usually includes the following steps: first, according to the required size and shape, a suitable ceramic material is selected as the base; then, the material is processed into the shape of the sagger through a molding process, such as pressing or injection molding; then, it is sintered at high temperature to give the sagger a certain strength and stability; finally, the sagger is finely processed and tested to ensure that it meets the requirements for use.
[0005] However, the traditional saggers used for sintering positive electrode materials for sodium-ion batteries also have some disadvantages. For example, the interface reaction between the sagger and the positive electrode material may affect the performance of the material; the sagger may undergo slight deformation at high temperatures, resulting in cracks or deformation in the sintered material; in addition, the repeated use of the sagger may cause wear and contamination on its surface, thus affecting the sintering effect. Therefore, these disadvantages need to be considered when preparing the sagger, and corresponding measures need to be taken to improve and optimize it. Summary of the invention
[0006] The object of the present invention is to provide a sagger for sintering positive electrode materials of a sodium ion battery and a preparation method thereof, so as to solve the problems existing in the prior art.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0008] The invention discloses a sagger for sintering positive electrode materials of a sodium ion battery. The sagger for sintering positive electrode materials of a sodium ion battery is prepared by immersing a substrate layer in a surface coating slurry, followed by drying and high-temperature sintering.
[0009] Preferably, the matrix layer is obtained by mixing mullite, alumina, cordierite and modified refractory materials and pressing them into blanks; the modified refractory materials are obtained by mixing magnesia calcium sand, magnesia sand, ultrafine flake graphite and modified carbon nanotubes; the modified carbon nanotubes are obtained by reacting carbon nanotubes and ferric nitrate.
[0010] Preferably, the surface coating slurry is obtained by mixing strontium carbonate, modified alumina, silicon carbide and silicon nitride; and the modified alumina is obtained by reacting hollow alumina microspheres and zirconium butoxide.
[0011] A method for preparing a sagger for sintering a positive electrode material of a sodium ion battery comprises the following preparation steps:
[0012] (1) Weighing carbon nanotubes and 0.2 mol / L ferric nitrate solution at a mass ratio of 1:30, mixing carbon nanotubes and 98 wt% concentrated hydrochloric acid at a mass ratio of 1:20, heating to 100°C for 4 h, filtering and dispersing into 0.2 mol / L ferric nitrate solution after the reaction, adjusting the pH to 10 with 28 wt% ammonia water, filtering and washing with pure water for 3 times, drying at 105°C, and calcining at 450°C for 2 h to obtain modified carbon nanotubes;
[0013] (2) Weighing ultrafine flake graphite, modified carbon nanotubes, magnesia sand, binder, and magnesia calcium sand; ball-milling the ultrafine flake graphite and modified carbon nanotubes for 1 hour to obtain a premixed fine powder, then adding the magnesia calcium sand and magnesia sand to a mixing mill, then adding 50% of the binder for mixing and milling, then adding the premixed fine powder and the remaining binder, mixing and milling, and curing at 220° C. for 12 hours to obtain a refractory material;
[0014] (3) Weigh 30-40 parts of mullite, 20-25 parts of cordierite, 10-12 parts of sintered alumina powder, 5-7 parts of activated alumina powder, 8-12 parts of refractory material, 2-5 parts of yellow dextrin and 5-7 parts of pure water by weight, mix them evenly, and use a wet mill to mix for 20 minutes; use a single-column hydraulic press to press them into a 25mm*25mm*125mm green body at a pressure of 150MPa; keep the green body at 60°C for 6 hours, and then keep it at 110°C for 24 hours; obtain a substrate layer;
[0015] (4) Weighing alumina hollow microspheres, ethanol, zirconium butoxide, and 2 mol / L acetic acid solution in a mass ratio of 1:20:1.5:2, mixing the alumina hollow microspheres and ethanol, ultrasonicating for 10 min, adding zirconium butoxide and continuing to stir, then adding 2 mol / L acetic acid solution, continuing to stir for 2 h, and then standing for 2 h, filtering and drying, and treating at 1100 ° C. for 5 h to obtain modified alumina;
[0016] (5) adding 50-60 parts of pure water to 5-10 parts of strontium carbonate, 8-12 parts of modified alumina, 20-30 parts of silicon carbide powder, 10-20 parts of silicon nitride powder, and 4-6 parts of carboxymethyl cellulose by weight, and ball milling for 60-80 minutes, and then adding 10-12 parts of pure water and stirring evenly to obtain a surface coating slurry;
[0017] (6) The substrate layer is immersed in the surface coating slurry and then taken out, the thickness of the slurry is 0.1-0.2 mm, and then dried and sintered to obtain a sagger for sintering positive electrode materials for sodium ion batteries.
[0018] Preferably, the carbon nanotubes in step (1) are single-walled carbon nanotubes with a diameter of 60-100 nm and a length of 5-20 μm.
[0019] Preferably, the mass ratio of the ultrafine flake graphite, modified carbon nanotubes, magnesia, binder and magnesium calcium sand in step (2) is 1.5:(1.5-2.0):35:3.5:70.
[0020] Preferably, the ultrafine flake graphite particle size of step (2) is 6-14 μm; the magnesia sand particle size is <0.088 mm; the binder model is phenolic resin FRJ-551; the magnesia calcium sand is obtained by mixing magnesia calcium sand with a particle size of 0-1 mm, magnesia calcium sand with a particle size of 1-3 mm, and magnesia calcium sand with a particle size of 3-5 mm in a mass ratio of 2:3:2.
[0021] Preferably, the mullite particle size in step (3) is 200 mesh; the cordierite particle size is 0.3-2.5 mm; the sintered alumina model is T60, purchased from Almatis Aluminum (Qingdao) Co., Ltd.; the activated alumina model is CL370, purchased from Almatis Aluminum (Qingdao) Co., Ltd.
[0022] Preferably, the alumina hollow microspheres in step (4) have a particle size of 1.3 μm and are purchased from Kaifeng Gaoda Furnace Material Co., Ltd.
[0023] Preferably, the silicon carbide powder in step (5) has a particle size of 0.3-0.5 μm; the silicon nitride powder is model SN-E10, purchased from Ube, Japan.
[0024] Preferably, in step (6), the drying temperature is 80-90° C., and the drying time is 12-16 h; the sintering temperature is 1200° C., and the sintering time is 4-5 h.
[0025] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0026] The sagger for sintering positive electrode materials of sodium ion batteries prepared by the present invention comprises a base layer and a surface coating slurry, wherein the base layer is obtained by mixing mullite, alumina, cordierite and a modified refractory material, and the surface coating slurry is obtained by mixing strontium carbonate, modified alumina, silicon carbide and silicon nitride. The base layer is immersed in the surface coating slurry, and then dried and sintered at high temperature to obtain the sagger for sintering positive electrode materials of sodium ion batteries.
[0027] First, carbon nanotubes and ferric nitrate are reacted to obtain modified carbon nanotubes, and magnesium calcium sand, magnesium sand, ultrafine flake graphite and modified carbon nanotubes are mixed in the presence of a binder to obtain a modified refractory material; carbon nanotubes are used as a carbon source and magnesium calcium to obtain magnesium calcium carbon material; as an alkaline refractory material, magnesium calcium material has high corrosion resistance and high density in an alkaline environment and has excellent refractory properties; however, the strength of magnesium calcium material is not high and it is easy to hydrate. The surface of the modified carbon nanotubes obtained by the reaction of carbon nanotubes and ferric nitrate contains uniformly distributed iron oxide, and the carbon nanotubes can improve the mechanical properties of the magnesium calcium material. In addition to being a catalyst that allows phenolic resin binders to form stable crystalline carbon during high-temperature carbonization, thereby further improving the mechanical properties, iron oxide can also increase liquid phase sintering, improve the hydration resistance of the magnesium calcium material, and promote the densification of the magnesium calcium material; mullite, alumina, cordierite and modified refractory materials are mixed to form a matrix layer with good mechanical properties.
[0028] Secondly, hollow alumina microspheres are reacted with zirconium butoxide to obtain hollow alumina microspheres with zirconium oxide coated on the surface. The hollow alumina microspheres are lightweight and have a hollow structure inside, which can provide good thermal insulation. This feature protects the inside of the sagger from high temperature damage when used in a high-temperature environment, thereby extending the service life of the sagger. However, the strength of the hollow alumina microspheres is relatively low, and the hollow alumina microspheres are easily damaged during the pressing and even mixing process. By reacting the hollow alumina microspheres and zirconium butoxide to coat the surface of the microspheres with a layer of high-strength zirconium oxide, not only the strength of the hollow microspheres can be improved, but the strong corrosion resistance of zirconium oxide can also enhance the erosion resistance of the sagger. Then, strontium carbonate, modified alumina, silicon carbide and silicon nitride are mixed to obtain a surface coating slurry.
[0029] Finally, the base layer is immersed in the surface coating slurry, and then dried and sintered at high temperature to obtain a sagger for sintering positive electrode materials of sodium ion batteries; the addition of strontium carbonate and the strontium oxide generated during the sintering process react with the magnesium oxide, aluminum oxide and other components in the base layer to form a compound, and then develop into an interlocking structure. The appearance of this structure is conducive to enhancing the structure of the surface coating and the base layer, and it is not easy to fall off during use; the addition of silicon carbide and silicon nitride can give the sagger good antioxidant ability. The silicon dioxide generated by silicon and oxygen reacts with the magnesium oxide in the base layer to form a compound phase, which blocks the pores and prevents further oxidation of the material. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0031] The material lists in all the following embodiments and comparative examples are as follows:
[0032] The carbon nanotubes are single-walled carbon nanotubes with a diameter of 60-100 nm and a length of 5-20 μm;
[0033] The particle size of ultrafine flake graphite is 6-14μm;
[0034] Magnesium sand particle size <0.088mm;
[0035] The binder model is phenolic resin FRJ-551;
[0036] The magnesium calcium sand is obtained by mixing magnesium calcium sand with a particle size of 0-1 mm, magnesium calcium sand with a particle size of 1-3 mm, and magnesium calcium sand with a particle size of 3-5 mm in a mass ratio of 2:3:2;
[0037] The mullite particle size is 200 mesh;
[0038] The particle size of cordierite is 0.3-2.5mm;
[0039] The sintered alumina model was T60, purchased from Anmai Aluminum (Qingdao) Co., Ltd.;
[0040] The activated alumina model was CL370, purchased from Anmai Aluminum (Qingdao) Co., Ltd.;
[0041] Alumina hollow microspheres with a particle size of 1.3 μm were purchased from Kaifeng Gaoda Furnace Material Co., Ltd.
[0042] The particle size of silicon carbide powder is 0.3-0.5μm;
[0043] The silicon nitride powder model is SN-E10, purchased from Ube, Japan.
[0044] Embodiment 1:
[0045] A method for preparing a sagger for sintering a positive electrode material of a sodium ion battery, the method comprising the following preparation steps:
[0046] (1) Weigh carbon nanotubes and 0.2 mol / L ferric nitrate solution at a mass ratio of 1:30, mix carbon nanotubes and 98 wt% concentrated hydrochloric acid at a mass ratio of 1:20, heat to 100°C and react for 4 h. After the reaction, filter and disperse into 0.2 mol / L ferric nitrate solution, adjust the pH to 10 with 28 wt% ammonia water, filter and wash with pure water for 3 times, dry at 105°C, and calcine at 450°C for 2 h to obtain modified carbon nanotubes.
[0047] (2) Weigh ultrafine flake graphite, modified carbon nanotubes, magnesia sand, binder, and magnesium calcium sand in a mass ratio of 1.5:1.5:35:3.5:70; ball-mill the ultrafine flake graphite and modified carbon nanotubes for 1 hour to mix evenly to obtain a premixed fine powder; then add the magnesium calcium sand and magnesia sand into a mixer and then add 50% of the binder for mixing and milling; then add the premixed fine powder and the remaining binder; after mixing and milling evenly, cure at 220°C for 12 hours to obtain a refractory material.
[0048] (3) According to the mass percentage, 30 parts of mullite, 20 parts of cordierite, 10 parts of sintered alumina powder, 5 parts of activated alumina powder, 8 parts of refractory materials, 2 parts of yellow dextrin and 5 parts of pure water were weighed and mixed evenly, and mixed using a wet mill for 20 minutes; a single-column hydraulic press was used to press the green body of 25 mm*25 mm*125 mm at a pressure of 150 MPa; the green body was kept at 60°C for 6 hours, and then kept at 110°C for 24 hours; and a substrate layer was obtained.
[0049] (4) Alumina hollow microspheres, ethanol, zirconium butoxide, and 2 mol / L acetic acid solution were weighed in a mass ratio of 1:20:1.5:2, the alumina hollow microspheres and ethanol were mixed, ultrasonicated for 10 min, zirconium butoxide was added and continued to be stirred, and then 2 mol / L acetic acid solution was added and continued to be stirred for 2 h. The mixture was allowed to stand for 2 h, filtered and dried, and treated at 1100° C. for 5 h to obtain modified alumina.
[0050] (5) By weight, 5 parts of strontium carbonate, 8 parts of modified alumina, 20 parts of silicon carbide powder, 10 parts of silicon nitride powder, and 4 parts of carboxymethyl cellulose were added to 50 parts of pure water and ball-milled for 60 minutes. Then, 10 parts of pure water was added and stirred evenly to obtain a surface coating slurry.
[0051] (6) After the substrate layer is immersed in the surface coating slurry, it is taken out, the thickness of the slurry is 0.2 mm, and then dried at 80°C for 12 hours; sintered at 1200°C for 5 hours to obtain a sagger for sintering positive electrode materials for sodium ion batteries.
[0052] Embodiment 2:
[0053] A method for preparing a sagger for sintering a positive electrode material of a sodium ion battery, the method comprising the following preparation steps:
[0054] (1) Weigh carbon nanotubes and 0.2 mol / L ferric nitrate solution at a mass ratio of 1:30, mix carbon nanotubes and 98 wt% concentrated hydrochloric acid at a mass ratio of 1:20, heat to 100°C and react for 4 h. After the reaction, filter and disperse into 0.2 mol / L ferric nitrate solution, adjust the pH to 10 with 28 wt% ammonia water, filter and wash with pure water for 3 times, dry at 105°C, and calcine at 450°C for 2 h to obtain modified carbon nanotubes.
[0055] (2) Weigh ultrafine flake graphite, modified carbon nanotubes, magnesia sand, binder, and magnesium calcium sand in a mass ratio of 1.5:1.7:35:3.5:70; ball-mill the ultrafine flake graphite and modified carbon nanotubes for 1 hour to mix evenly to obtain a premixed fine powder; then add the magnesium calcium sand and magnesia sand into a mixer and then add 50% of the binder for mixing and grinding; then add the premixed fine powder and the remaining binder; after mixing and grinding evenly, cure at 220°C for 12 hours to obtain a refractory material.
[0056] (3) Weigh 35 parts of mullite, 22 parts of cordierite, 11 parts of sintered alumina powder, 6 parts of activated alumina powder, 10 parts of refractory materials, 3 parts of yellow dextrin and 6 parts of pure water by mass, mix them evenly, and use a wet mill to mix for 20 minutes; use a single-column hydraulic press to press them into a 25mm*25mm*125mm green body at a pressure of 150MPa; keep the green body at 60℃ for 6 hours, and then keep it at 110℃ for 24 hours; obtain a substrate layer.
[0057] (4) Alumina hollow microspheres, ethanol, zirconium butoxide, and 2 mol / L acetic acid solution were weighed in a mass ratio of 1:20:1.5:2, the alumina hollow microspheres and ethanol were mixed, ultrasonicated for 10 min, zirconium butoxide was added and continued to be stirred, and then 2 mol / L acetic acid solution was added and continued to be stirred for 2 h. The mixture was allowed to stand for 2 h, filtered and dried, and treated at 1100° C. for 5 h to obtain modified alumina.
[0058] (5) By weight, 7 parts of strontium carbonate, 10 parts of modified alumina, 25 parts of silicon carbide powder, 15 parts of silicon nitride powder, and 5 parts of carboxymethyl cellulose were added to 55 parts of pure water and ball-milled for 70 minutes. Then, 11 parts of pure water were added and stirred evenly to obtain a surface coating slurry.
[0059] (6) The substrate layer is immersed in the surface coating slurry and then taken out, the thickness of the slurry is 0.15 mm, and then dried at a drying temperature of 85° C. and a drying time of 15 h; sintered at a sintering temperature of 1200° C. and a sintering time of 4.5 h to obtain a sagger for sintering positive electrode materials for sodium ion batteries.
[0060] Embodiment 3:
[0061] A method for preparing a sagger for sintering a positive electrode material of a sodium ion battery, the method comprising the following preparation steps:
[0062] (1) Weigh carbon nanotubes and 0.2 mol / L ferric nitrate solution at a mass ratio of 1:30, mix carbon nanotubes and 98 wt% concentrated hydrochloric acid at a mass ratio of 1:20, heat to 100°C and react for 4 h. After the reaction, filter and disperse into 0.2 mol / L ferric nitrate solution, adjust the pH to 10 with 28 wt% ammonia water, filter and wash with pure water for 3 times, dry at 105°C, and calcine at 450°C for 2 h to obtain modified carbon nanotubes.
[0063] (2) Ultrafine flake graphite, modified carbon nanotubes, magnesia sand, binder, and magnesium calcium sand are weighed in a mass ratio of 1.5:2.0:35:3.5:70; the ultrafine flake graphite and modified carbon nanotubes are ball-milled for 1 hour to obtain a premixed fine powder; the magnesium calcium sand and magnesia sand are added to a mixer and then 50% of the binder is added for mixing and milling; the premixed fine powder and the remaining binder are added; the mixture is mixed and milled and then cured at 220° C. for 12 hours to obtain a refractory material.
[0064] (3) According to the mass percentage, 40 parts of mullite, 25 parts of cordierite, 12 parts of sintered alumina powder, 7 parts of activated alumina powder, 12 parts of refractory materials, 5 parts of yellow dextrin and 7 parts of pure water were weighed and mixed evenly, and mixed using a wet mill for 20 minutes; a single-column hydraulic press was used to press the green body of 25 mm*25 mm*125 mm at a pressure of 150 MPa; the green body was kept at 60°C for 6 hours, and then kept at 110°C for 24 hours; and a substrate layer was obtained.
[0065] (4) Alumina hollow microspheres, ethanol, zirconium butoxide, and 2 mol / L acetic acid solution were weighed in a mass ratio of 1:20:1.5:2, the alumina hollow microspheres and ethanol were mixed, ultrasonicated for 10 min, zirconium butoxide was added and continued to be stirred, and then 2 mol / L acetic acid solution was added and continued to be stirred for 2 h. The mixture was allowed to stand for 2 h, filtered and dried, and treated at 1100° C. for 5 h to obtain modified alumina.
[0066] (5) By weight, 10 parts of strontium carbonate, 12 parts of modified alumina, 30 parts of silicon carbide powder, 20 parts of silicon nitride powder, and 6 parts of carboxymethyl cellulose were added to 60 parts of pure water and ball-milled for 60 minutes. Then, 12 parts of pure water were added and stirred evenly to obtain a surface coating slurry.
[0067] (6) After the substrate layer is immersed in the surface coating slurry, it is taken out, the thickness of the slurry is 0.1 mm, and then dried at 80°C for 12 hours; sintered at 1200°C for 4 hours to obtain a sagger for sintering positive electrode materials for sodium ion batteries.
[0068] Comparative Example 1:
[0069] The preparation method of the sagger for sintering the positive electrode material of the sodium ion battery of the comparative example 1 is different from that of the embodiment 2 in that step (1) is not performed, and step (2) is modified as follows: ultrafine flake graphite, magnesia, binder, and magnesium calcium sand are weighed in a mass ratio of 1.5:35:3.5:70; the ultrafine flake graphite is ball-milled for 1 hour and mixed evenly to obtain a premixed fine powder, and then the magnesium calcium sand and magnesia are added to a mixing mill and then 50% of the binder is added for mixing and grinding, and then the premixed fine powder and the remaining binder are added, and after mixing and grinding evenly, the mixture is cured at 220° C. for 12 hours to obtain a refractory material.
[0070] Comparative Example 2:
[0071] The preparation method of the sagger for sintering the positive electrode material of a sodium ion battery in Comparative Example 2 differs from that in Example 2 in that it does not contain steps (4) to (5), and step (6) is modified as follows: drying the substrate at a drying temperature of 85° C. for a drying time of 15 h; sintering at a sintering temperature of 1200° C. for a sintering time of 4-5 h to obtain a sagger for sintering the positive electrode material of a sodium ion battery.
[0072] Test Example 1:
[0073] Mechanical properties test: The high temperature flexural strength of the sagger was tested according to GB / T 5072-2023, at a temperature of 1100°C and a time of 60 minutes. The results are shown in Table 1.
[0074] Table 1 Statistical results of mechanical properties test
[0075] High temperature flexural strength / MPa High temperature flexural strength / MPa Example 1 14.01 Comparative Example 1 10.31 Example 2 15.34 Comparative Example 2 9.74 Example 3 15.97
[0076] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 2 in Table 1, it can be found that the sagger for sintering the positive electrode material of the sodium ion battery prepared in the present invention has good mechanical properties.
[0077] By comparing the data in the table, the mechanical properties of the embodiment are better than those of the comparative example, which shows that the modified carbon nanotubes are prepared by reacting carbon nanotubes with ferric nitrate, and the modified refractory material is prepared by mixing magnesium calcium sand, magnesium sand, ultrafine flake graphite and modified carbon nanotubes in the presence of a binder; the magnesium calcium carbon material is obtained by using carbon nanotubes as a carbon source and magnesium calcium. The strength of the magnesium calcium material is not high and it is easy to hydrate. The surface of the modified carbon nanotubes prepared by the reaction of carbon nanotubes with ferric nitrate contains uniformly distributed iron oxide. The carbon nanotubes can improve the mechanical properties of the magnesium calcium material. In addition to serving as a catalyst to form stable crystalline carbon when the phenolic resin binder is carbonized at high temperature, the iron oxide can also increase liquid phase sintering, improve the hydration resistance of the magnesium calcium material, and promote the densification of the magnesium calcium material.
[0078] Test Example 2:
[0079] Corrosion resistance test: Sodium manganate positive electrode material was used for corrosion resistance test. Sodium carbonate and manganese carbonate were weighed according to n(Na):n(Mn)=1:1, and the positive electrode material precursor was obtained after being mixed evenly. The precursor with a mass of 0.5 times of the sagger was placed on the surface of the sagger, calcined at 1100℃ for 36h for corrosion reaction, and the surface condition of the sagger was recorded. The results are shown in Table 2.
[0080] Table 2 Statistical results of corrosion resistance test
[0081] Surface condition of sagger Surface condition of sagger Example 1 intact Comparative Example 1 crack Example 2 intact Comparative Example 2 crack Example 3 intact
[0082] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 2, it can be found that the sagger for sintering the positive electrode material of the sodium ion battery prepared by the present invention has excellent corrosion resistance.
[0083] By comparing the data in the table, the erosion resistance of the embodiment is better than that of the comparative example, indicating that the hollow alumina microspheres and zirconium butoxide are reacted to obtain hollow alumina microspheres with zirconium oxide coated on the surface; the strong corrosion resistance of zirconium oxide can enhance the erosion resistance of the sagger.
[0084] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A sagger for sintering positive electrode materials for sodium ion batteries, characterized in that: The sagger for sintering the positive electrode material of the sodium ion battery is made by immersing the substrate layer in the surface coating slurry, and then drying and sintering at high temperature; The matrix layer is obtained by mixing mullite, alumina, cordierite and modified refractory materials and pressing them into blanks; the modified refractory materials are obtained by mixing magnesia calcium sand, magnesia sand, ultrafine flake graphite and modified carbon nanotubes; the modified carbon nanotubes are obtained by reacting carbon nanotubes and ferric nitrate; The surface coating slurry is obtained by mixing strontium carbonate, modified alumina, silicon carbide and silicon nitride; the modified alumina is obtained by reacting hollow alumina microspheres and zirconium butoxide.
2. A method for preparing a sagger for sintering a positive electrode material for a sodium ion battery, characterized in that: The method comprises the following preparation steps: (1) Weighing carbon nanotubes and 0.2 mol / L ferric nitrate solution at a mass ratio of 1:30, mixing carbon nanotubes and 98 wt% concentrated hydrochloric acid at a mass ratio of 1:20, heating to 100°C for 4 h, filtering and dispersing into 0.2 mol / L ferric nitrate solution after the reaction, adjusting the pH to 10 with 28 wt% ammonia water, filtering and washing with pure water for 3 times, drying at 105°C, and calcining at 450°C for 2 h to obtain modified carbon nanotubes; (2) Weighing ultrafine flake graphite, modified carbon nanotubes, magnesia sand, binder, and magnesia calcium sand; ball-milling the ultrafine flake graphite and modified carbon nanotubes for 1 hour to obtain a premixed fine powder, then adding the magnesia calcium sand and magnesia sand to a mixing mill, then adding 50% of the binder for mixing and milling, then adding the premixed fine powder and the remaining binder, mixing and milling, and curing at 220° C. for 12 hours to obtain a refractory material; (3) Weigh 30-40 parts of mullite, 20-25 parts of cordierite, 10-12 parts of sintered alumina powder, 5-7 parts of activated alumina powder, 8-12 parts of refractory material, 2-5 parts of yellow dextrin and 5-7 parts of pure water by weight, mix them evenly, and use a wet mill to mix for 20 minutes; use a single-column hydraulic press to press them into a 25mm*25mm*125mm green body at a pressure of 150MPa; keep the green body at 60°C for 6 hours, and then keep it at 110°C for 24 hours; obtain a substrate layer; (4) Weighing alumina hollow microspheres, ethanol, zirconium butoxide, and 2 mol / L acetic acid solution in a mass ratio of 1:20:1.5:2, mixing the alumina hollow microspheres and ethanol, ultrasonicating for 10 min, adding zirconium butoxide and continuing to stir, then adding 2 mol / L acetic acid solution, continuing to stir for 2 h, and then standing for 2 h, filtering and drying, and treating at 1100 ° C. for 5 h to obtain modified alumina; (5) adding 50-60 parts of pure water to 5-10 parts of strontium carbonate, 8-12 parts of modified alumina, 20-30 parts of silicon carbide powder, 10-20 parts of silicon nitride powder, and 4-6 parts of carboxymethyl cellulose by weight, and ball milling for 60-80 minutes, and then adding 10-12 parts of pure water and stirring evenly to obtain a surface coating slurry; (6) The substrate layer is immersed in the surface coating slurry and then taken out, the thickness of the slurry is 0.1-0.2 mm, and then dried and sintered to obtain a sagger for sintering positive electrode materials for sodium ion batteries.
3. The method for preparing a sagger for sintering a positive electrode material for a sodium ion battery according to claim 2, characterized in that: The carbon nanotubes in step (1) are single-walled carbon nanotubes with a diameter of 60-100 nm and a length of 5-20 μm.
4. The method for preparing a sagger for sintering a positive electrode material for a sodium ion battery according to claim 2, characterized in that: The mass ratio of the ultrafine flake graphite, modified carbon nanotubes, magnesia sand, binder and magnesia calcium sand in step (2) is 1.5:(1.5-2.0):35:3.5:
70.
5. The method for preparing a sagger for sintering a positive electrode material for a sodium ion battery according to claim 2, characterized in that: The particle size of the ultrafine flake graphite in the step (2) is 6-14 μm; the particle size of the magnesia sand is <0.088 mm; the model of the binder is phenolic resin FRJ-551; the magnesia calcium sand is obtained by mixing magnesia calcium sand with a particle size of 0-1 mm, magnesia calcium sand with a particle size of 1-3 mm, and magnesia calcium sand with a particle size of 3-5 mm in a mass ratio of 2:3:
2.
6. The method for preparing a sagger for sintering a positive electrode material for a sodium ion battery according to claim 2, characterized in that: In the step (3), the particle size of the mullite is 200 mesh; the particle size of the cordierite is 0.3-2.5 mm; the model of the sintered alumina is T60; and the model of the activated alumina is CL370.
7. The method for preparing a sagger for sintering a positive electrode material for a sodium ion battery according to claim 2, characterized in that: The particle size of the hollow alumina microspheres in step (4) is 1.3 μm.
8. The method for preparing a sagger for sintering a positive electrode material for a sodium ion battery according to claim 2, characterized in that: The particle size of the silicon carbide powder in step (5) is 0.3-0.5 μm; the model of the silicon nitride powder is SN-E10.
9. The method for preparing a sagger for sintering a positive electrode material for a sodium ion battery according to claim 5, characterized in that: In the step (6), the drying temperature is 80-90°C, and the drying time is 12-16 hours; the sintering temperature is 1200°C, and the sintering time is 4-5 hours.
Citation Information
Patent Citations
Corundum mullite slab for high temperature and preparation method thereof
CN108298963A
Lightweight saggar for roasting positive electrode material of lithium battery and preparation method thereof
CN108373324A
Special sagger for sintering lithium battery positive electrode material and preparation method of sagger
CN110540418A
Production method of mullite sagger
CN112239366A
Sagger for positive electrode material of lithium ion battery and preparation method of sagger
CN114195533A